Factors Associated with the Retention and Migration that Influence Senior High School Graduates in Amando Cope College - Engay, Federico B. (International Journal of Research in Interdisciplinary Studies, 2025)
This study determined the manifested factors influencing the retention and migration of senior high school graduates in Amando Cope College starting its implementation on SY 2016-2017 up to present. The following conclusions are derived: Older students may have greater maturity, which can influence how they weigh their options regarding where to pursue college and might actively seek independence and choose to migrate, while younger students might be less ready for relocation, preferring to stay in a familiar environment like Amando Cope College; Sex plays a potentially important role in understanding pattern of retention and migration among senior high school graduates; parental earnings and parents’ educational attainment plays a critical role in shaping the post-senior high school educational decisions of students and a significant factor that can greatly influence their children’s academic decisions and aspirations; factors influencing the retention of SHS graduates, student’s positive past experience during their senior high school (SHS) years in Amando Cope College have powerful influence on their decision to either stay for college or leave for another institution these experiences, both academic and non-academic, shape the students’ perceptions of the college environment, support systems, and overall value. Factors influencing the migration of SHS graduates describe the learning environment as the most influential factor that affect their decision to migrate to other institutions. Physical setting, classroom atmosphere, availability of learning resources, quality of instruction, and overall academic culture plays a pivotal role in shaping students’ educational experiences and future decisions. Various recommendations were offered to the school administrators by the researcher upon the completion of the study.